Are you with me? Co-occurrence tests from community ecology can identify positive and negative epistasis between inversions in Mimulus guttatus - Luis J. Madrigal-Roca; John K. Kelly (PLoS ONE, 2025)
Chromosomal inversions are structural genetic variants that can play a crucial role in adaptive evolution and speciation. Patterns of attraction and repulsion among unlinked inversions — whether they tend to be carried by the same or different individuals— can indicate how selection is acting on these polymorphisms. In this study, we compare analytical techniques using data from 64 inversions that segregate among 1373 F2 plants of the yellow monkeyflower Mimulus guttatus. Mendelian assortment provides a strong null hypothesis for χ2 contingency tests. Here, we show how co-occurrence metrics used in community ecology can provide additional insight regarding coupling and repulsion of inversions at genotypic level. The centered Jaccard/Tanimoto index and the affinity score describe the specific way that inversions interact to generate epistasis for plant survival. We further explore the use of network analysis to visualize inversion interactions and to identify essential third and fourth order interactions, which expand the traditional pairwise scope of the co-occurrence metrics. We suggest that a combination of different statistical approaches will provide the most complete characterization of the fitness effects, both for inversions and other polymorphisms essential to adaptation and speciation.